From COVID Vaccines to HIV Prevention: Pharmaceutical Financing and Distribution for the Public's Health. (2022) - Sharfstein, Joshua M.; Conti, Rena M.; Gee, Rebekah E.
Abstract: The complexity and inefficiency of the U.S. health care system complicates the distribution of life-saving medical technologies. When the public health is at stake, however, there are alternatives. The proposal for a national PrEP program published in this issue of the Journal applies some of the lessons of the national COVID vaccine campaign to HIV prevention. In doing so, it draws on other examples of public health approaches to the financing of medical technology, from vaccines for children to hepatitis C treatment.